Spatial gradients in freshwater fish diversity, abundance and current pattern in the Himalayan region of Upper Ganges Basin, India - AJEY KUMAR PATHAK; UTTAM KUMAR SARKAR; SHRI PRAKASH SINGH (Society for Indonesian Biodiversity, 2014)
Pathak AK, Sarkar UK, Singh SP. 2014. Spatial gradients in freshwater fish diversity, abundance and current pattern in the Himalayan region of Upper Ganges Basin, India. Biodiversitas 15: 186-194.The present study describes the analysis and mapping of the differentmeasurements of freshwater fish biodiversity of the Upper Ganges basin in the Himalayan region using spatial interpolation methods ofGeographical Information System. The diversity, richness and abundance of fishes for each sampling location were determined andKriging interpolation was applied on each fisheries measurement to predict and produce semivariogram. The semivariogarms producedwere cross validated and reclassified. The reclassified maps for richness, abundance and diversity of fishes, occurrence of cold waterthreatened fish and abundance of important genera like Tor, Schizothorax and species were produced. The result of the Krigingproduced good results and overall error in the estimation process was found significant. The cross validation of semovariograms alsoprovided a better result with the observed data sets. Moreover, weighted overlay analysis of the reclassified raster maps of richness andabundance of fishes produced the classified raster map at different evaluation scale (0-10) qualitatively describing the gradient ofspecies richness and abundance compositely. Similarly, the classified raster map at same evaluation scale qualitatively describing thegradient of species abundance and diversity compositely was produced and published. Further, basin wise analysis betweenAlaknanda/Pindar and Ganga1 sub basins showed 0.745 disparities at 0.745 distances in 2 dimensional spaces. The richness, diversityand abundance of threatened fishes among the different sampling locations were not significant (p = 0.9).